Aberrant individual structure covariance network in patients with mesial temporal lobe epilepsy - Huang, Yuda; Wang, Ningrui; Li, Wei; Feng, Tao; Zhang, Huaqiang; Fan, Xiaotong; Chen, Sichang; Wang, Yihe; Shan, Yongzhi; Wei, Penghu; Zhao, Guoguang (Frontiers in Neuroscience, 2024)
Objective: Mesial temporal lobe epilepsy (mTLE) is a complex neurological disorder that has been recognized as a widespread global network disorder. The group-level structural covariance network (SCN) could reveal the structural connectivity disruption of the mTLE but could not reflect the heterogeneity at the individual level.Methods: This study adopted a recently proposed individual structural covariance network (IDSCN) method to clarify the alternated structural covariance connection mode in mTLE and to associate IDSCN features with the clinical manifestations and regional brain atrophy.We found significant IDSCN abnormalities in the ipsilesional hippocampus, ipsilesional precentral gyrus, bilateral caudate, and putamen in mTLE patients than in healthy controls. Moreover, the IDSCNs of these areas were positively correlated with the gray matter atrophy rate. Finally, we identified several connectivities with weak associations with disease duration, frequency, and surgery outcome.